Studi Pengembangan Perparkiran di Kota Baubau - Muhammad Yusri Lukman; Muhammad Ikhsan Andi; Muhammad Zaki (Universitas Muslim Indonesia, 2017)
The increase in development in every city, especially business centers, has not been able to provide sufficient parking space, so that thesurrounding road bodies are used for parking lots. If the road body is passed by a large enough amount of traffic, it can be ensured that parking onthe road body will cause traffic problems (speed decreases and travel time increases. The emergence of parking problems in big cities invites thepublic and experts to think and really understand the parking system. The concept and characteristics of parking, analysis of parking needs,geometric planning of parking lots, and parking policies are one of the ideas that can be implemented to deal with parking problems, especially inBaubau City. This study aims to examine the feasibility of the best, optimal parking location and have good prospects for the development of theBaubau City area, Examine the socio-cultural feasibility of the community in relation to the plan Determination of parking locations, both microscale (socio-cultural feasibility in selected locations) and macro scale (socio-cultural feasibility associated with Baubau City as a whole), Assessenvironmental feasibility at parking location points so that it does not environmental degradation occurs due to parking location planning,Examining economic aspects and taking into account the level of income at the time of operation of the parking system, estimating the investmentcost needed for the construction of the parking area and estimating the return on investment with rational and realistic assumptions. The datacollection method is carried out in two ways, namely secondary surveys and primary surveys.